The role of small extracelllular vesicles in endometriosis - Mohamed Nazri, NHM (2021)
Endometriosis, defined as endometrial-like tissue outside the uterus, causes pain and/ or subfertility in 10% of reproductive-age women (Zondervan, Becker and Missmer, 2020). To date, the cause is unknown, resulting in inadequate diagnostic methods and treatment options (E. Liu et al., 2015; Gupta et al., 2016; Nisenblat, Bossuyt, et al., 2016; Nisenblat, Prentice, et al., 2016).